The food of Paris : Delicious recipes from Parisian bistros and restaurants / Marie-Noël Rio - Rio, Marie-Noël
A collection of over 60 recipes from some of the celebrated eateries in Paris, including Chez Casimir, Brasserie Mollard and Le Troquet. It features location and recipe photography, detailed information on ingredients, and insights into the food culture of Paris